The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1507/endocrj.ej12-0108
|View full text |Cite
|
Sign up to set email alerts
|

Longer <i>HSD11B2</i> CA-repeat in impaired glucose tolerance and type 2 diabetes

Abstract: Abstract. Type 2 11β-hydroxysteroid dehydrogenase encoded by the HSD11B2 gene converts cortisol to inactive cortisone, and alteration in this enzymatic activity might affect glucose homeostasis by affecting circulating levels or tissue availability of glucocorticoids. We investigated the association of HSD11B2 variant with glucose homeostasis. Subjects with normal glucose tolerance (n=585), impaired glucose tolerance (n=202) and type 2 diabetes (n=355) were genotyped for a highly polymorphic CA-repeat polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Negative findings were yielded for HSD11B2 SNPs with adolescent obesity (Ruan et al, 2014 ); similarly, gene regulation studies identified only microRNA relevant to renal functioning (Rezaei et al, 2014 ). However, the polymorphic CA-repeat polymorphism in the first intron of HSD11B2 was significantly related to insulin insensitivity (Mune et al, 2013 ).…”
Section: Genomic Foundation Of Basic Regulatory Mechanisms In Metsmentioning
confidence: 99%
“…Negative findings were yielded for HSD11B2 SNPs with adolescent obesity (Ruan et al, 2014 ); similarly, gene regulation studies identified only microRNA relevant to renal functioning (Rezaei et al, 2014 ). However, the polymorphic CA-repeat polymorphism in the first intron of HSD11B2 was significantly related to insulin insensitivity (Mune et al, 2013 ).…”
Section: Genomic Foundation Of Basic Regulatory Mechanisms In Metsmentioning
confidence: 99%
“…For example, the HSD11B2 gene can encode type 2 11β-hydroxysteroid dehydrogenase and participate in intracellular homeostasis, and convert cortisol to cortisone. It is an inactive corticosteroid that can prevent obesity and high blood pressure (Mune et al 2013). In the present study, we found that LRPAP1, a gene related to myopia, was elevated in giant pandas, which provided a new clue for the giant pandas' poor eyesight (Aldahmesh et al 2013).…”
Section: Discussionmentioning
confidence: 55%
“…This polymorphism is much more frequent in the general population and was shown to affect cortisol plasma concentrations [11,16]. The HSD11B2[CA]n microsatellite polymorphism in the first intron is associated with sodium sensitive essential hypertension [11,17], impaired glucose tolerance and type 2 diabetes [16] and birth weight-adolescent blood pressure associations [18]. But polymorphisms in the gene have not been consistently associated with hypertension [11,17,19,20].…”
Section: Discussionmentioning
confidence: 99%